2007
DOI: 10.1627/jpi.50.195
|View full text |Cite
|
Sign up to set email alerts
|

超音波照射によるトリオレインとエタノールのエステル交換反応に与えるモル比,触媒濃度および温度の影響

Abstract: The transesterification of triolein with ethanol to make biodiesel fuel was investigated under ultrasonic irradiation to evaluate the effects of the amount of base catalyst (NaOH or KOH), molar ratio of ethanol to triolein, and temperature. Transesterifi cation of triolein with ethanol readily proceeded under 40 kHz ultrasonic irradiation and the most suitable condition at 25 C was a molar ratio of ethanol/triolein of 6/1, base catalyst concentration of 1 wt for both NaOH and KOH, and reaction time of less tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…In addition, the emulsion droplets would be smaller under ultrasonic irradiation. Smaller emulsion droplets will result increased contract surface area between the immiscible phases 21 . Thus, the use of ultrasonic irradiation in both phases simultaneously enhances the rate of reaction as well as shifting the equilibrium and resulting in higher conversion to biodiesel.…”
Section: 3mentioning
confidence: 99%
“…In addition, the emulsion droplets would be smaller under ultrasonic irradiation. Smaller emulsion droplets will result increased contract surface area between the immiscible phases 21 . Thus, the use of ultrasonic irradiation in both phases simultaneously enhances the rate of reaction as well as shifting the equilibrium and resulting in higher conversion to biodiesel.…”
Section: 3mentioning
confidence: 99%
“…Similar to the conventional method, variables such as the methanol/oil molar ratio, reaction time, and the catalyst concentration have a significant effect on the biodiesel yield. To determine the optimal condition, Hanh et al 12) evaluated these variables by transesterifying triolein with ethanol under ultrasonic irradiation. The optimal conditions were then identified.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in some literature the molar ratio of 6:1 was found to be the best conversion efficiency in transesterification of such oils using an alkali catalyst (Marchetti et al, 2007). Many scientists have studied the effect of catalyst amount on the conversion of oils or fats to FAME by transesterification (Freedman et al, 1984;Nye et al, 1983;Mittelbach and Trathnigg, 1990;Tomasevic and Siler-Marinkovic, 2003;Hanh et al, 2007;Felizardo et al, 2006). In general, they found that 0.3-1% alkali catalyst concentration resulted in successful conversion depending on the type of oil used.…”
Section: Resultsmentioning
confidence: 92%